2020
DOI: 10.2217/bmm-2020-0180
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mmp-2 and Its Inhibitor Timp-2 As Biomarkers for Susceptibility to Systemic Lupus Erythematosus

Abstract: Aim: To investigate the possible association between MMP-2 (−1575 G/A, −1306 C/T) and its inhibitor TIMP-2 (−418 G/C) functional polymorphisms with development of severity in systemic lupus erythematosus (SLE) patients. Materials & methods: 150 SLE patients and matched healthy controls were recruited. Polymorphisms were detected by PCR-RFLP and serum levels by ELISA. Results: Mean MMP-2 and TIMP-2 serum level and mRNA expression were significantly increased in SLE cases as compared with controls (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, more evidence showed that TIMP-2 and MMP-2 expressions could play an important role in the development of other diseases. MMP-2, TIMP-2, and MMP-2/TIMP-2 ratios may act as biomarkers for susceptibility to systemic lupus erythematosus (SLE) [41]. Pathogenesis of chronic rhinosinusitis might also be related to the regulation of MMP-2 and TIMP-2 expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more evidence showed that TIMP-2 and MMP-2 expressions could play an important role in the development of other diseases. MMP-2, TIMP-2, and MMP-2/TIMP-2 ratios may act as biomarkers for susceptibility to systemic lupus erythematosus (SLE) [41]. Pathogenesis of chronic rhinosinusitis might also be related to the regulation of MMP-2 and TIMP-2 expressions.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly found polymorphism is TNFα rs1800629, which is also associated with SLE, 128 IBD, 129 PD, 130 AR, 131 and IBS 132 . Other variants were found in more than one disease, namely, the IL1β rs16944 with UC 133 and AR, 131 the IL1RN rs2234663 with UC 129 and PD, 134 the IL6 rs1800795 with IBD 135 and IBS, 132 the TLR4 rs4986790 with IBD 136 and PD, 137 and finally, the TIMP2 rs8179090 with SLE 138 and PD 139 …”
Section: Autoimmune and Inflammatory Diseases Related To Ptbmentioning
confidence: 99%
“…In addition, cellular overexpression and elevated serum levels of these four endopeptidases were observed in a wide variety of pathologies in which CD95/CD95L signalling has also been shown to contribute. For instance, MMP-2/MMP-3/MMP-7 serum levels are significantly increased in SLE and associated with disease activity, while elevated serum levels of MMP-12 have been observed in other systemic autoimmune diseases such as rheumatoid arthritis and systemic scleroderma [59][60][61][62]. MMP-2, -3, -7 and -12 have been reported to be overexpressed and associated with tumour propagation and poor cancer prognosis [59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%